A fotossíntese em livros didáticos de ciências dos anos finais do ensino fundamental : imagens, textos e alfabetização científica - Silva, Iris Alessandra da (2024)
Images and texts are important and complementary resources for the communication of scientific ideas. From a didactic point of view, they are resources that have an indisputable importance for visualization, contribute to the illustration of various didact ic scientific texts and play a fundamental role in the constitution of didactic scientific ideas, in their conceptualization and with the potential to provide evidence and conditions for scientific literacy indicators to manifest themselves in the content. We will find in textbooks, generally, many photos, drawings and texts, which, in their different presentation configurations, become susceptible to different readings and analyses. The present work aims to analyze images as visual resources and texts on t he theme "photosynthesis" in textbooks of Natural Sciences approved in the Programa Nacional do Livro e do Material Didático (PNLD Brazilian Textbook Program) 2024 2027 edition and its potential to promote the process of scientific literacy. In this rese arch we will investigate: i ) the characteristics of illustrations and texts of the content of “photosynthesis” in books and texts , on the concept of photosynthesis, ii ) w hich scientific problems are detected in these images and texts and, iii ) what are the possibilities of these resources to promote students' AC (literacy indicators The methodology adopted for the analysis is based on Yin (2016), in which there are five stages of studying the object content, they are: compile, decompose, recomp ose (and arrange), interpret and conclude. The initial phase, of an exploratory and descriptive nature, sought to study the program implementation documents (PNLD), with the classification criteria of the analyzed collections, to locate images and texts to be analyzed. The second stage consisted of mapping the approved publishers and their pedagogical proposals presented in their collections of accepted works, launched by the program. In a third moment, the data analysis occurred with the observation of ill ustrations together with texts on photosynthesis . Regarding the fourth stage, t he collected illustrations were separated into 5 (five) categories called “Illustrative Groups”, they were : Estruturas Microscópicas Fotossintéticas, Representações de Sistemas Simples, Representações de Sistemas Complexos, Atividades Avaliativas e Práticas Experimentais For this, analyzes were carried out relating to space, concepts, illustrations, practical activities and exercises proposed on photosynthesis. To complement the analysis of the last two groups, the indicators of Sasseron and Carvalho (2008) were used, whose purpose is based on the applicability of the content’s function to the literacy process science and its respective potential in the teaching and learning process.